Commentary on Romans - Calvin, Jean, 1509-1564 (Theological foundations., 2022)
The Theological Foundations series highlights the enduring influence of prominent figures from church history. The present volume features John Calvin's Commentary on Romans, along with an introduction by series editor Timothy George that explores the life, ministry, and scholarship of the French reformer.